IDENTIFIYING AND ANALYZING MISCONCEPTION OF XI GRADE STUDENTS ABOUT BASIC KINEMATICS MATERIAL BY USING TWO TIER-TEST METHOD IN SMA NEGERI 1 PERCUT SEI TUAN - Solikin; Threxy Febrina Br. Bukit; Eltera; Glen Adetya Purba; Esther Bertha Advent Nita Pardede; Fadila Fatimah; Ruth Brinets Sri Debora Hutagalung; Ruth Tamariska BR. Munthe; Wan Aura Cahyani (SULTAN ADAM: Jurnal Hukum dan Sosial, 2026)
Conceptual difficulties in fundamental physics, particularly basic kinematics, represent a persistent challenge in secondary education that significantly hinders students' subsequent learning. Misconceptions are alternative frameworks students hold that deviate from scientifically accepted concepts, often leading to systematic errors when solving problems or interpreting phenomena. Addressing this issue is critical, as a weak foundation in kinematics the description of motion can severely impact the comprehension of dynamics and energy. This study was specifically aimed at identifying and quantitatively analyzing the prevalence and patterns of student understanding and misconceptions regarding basic kinematics among 11th-grade science students at SMA Negeri 1 Percut Sei Tuan.The research employed a descriptive quantitative methodology, utilizing the robust Two-Tier Diagnostic Test method to collect and categorize student data. The study sample consisted of 30 students from the Grade XI Matlangraf class who participated in a 10-item questionnaire covering core kinematics concepts. Analysis of the diagnostic test results revealed a critical issue in conceptual mastery. The findings indicated that only 6 students (20%) demonstrated a solid conceptual understanding. Conversely, a significant majority 17 students (57%) were classified as experiencing specific misconceptions, while the remaining 7 students (23%) showed no understanding of the concepts. This substantial finding confirms that a majority of the 11th-grade cohort harbors underlying misconceptions related to basic kinematics material, underscoring the urgent necessity for the implementation of effective intervention strategies to address these cognitive obstacles directly.